2022
DOI: 10.1073/pnas.2201655119
|View full text |Cite
|
Sign up to set email alerts
|

How musical rhythm training improves short-term memory for faces

Abstract: Playing a musical instrument engages numerous cognitive abilities, including sensory perception, selective attention, and short-term memory. Mounting evidence indicates that engaging these cognitive functions during musical training will improve performance of these same functions. Yet, it remains unclear the extent these benefits may extend to nonmusical tasks, and what neural mechanisms may enable such transfer. Here, we conducted a preregistered randomized clinical trial where nonmusicians underwent 8 wk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 117 publications
0
5
1
Order By: Relevance
“…In contrast to our null effect of rhythm training on working memory, we recently observed that digital rhythm training can improve short‐term memory for faces in older adults (Zanto et al., 2022). Although more research will be needed to understand the specificity of rhythm training on memory ability, there are several reasons why rhythm training may differentially affect memory.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our null effect of rhythm training on working memory, we recently observed that digital rhythm training can improve short‐term memory for faces in older adults (Zanto et al., 2022). Although more research will be needed to understand the specificity of rhythm training on memory ability, there are several reasons why rhythm training may differentially affect memory.…”
Section: Discussioncontrasting
confidence: 99%
“…Musical rhythm training was conducted using a custom-designed video game, Coherence (Figure 1). Coherence was created at UCSF Neuroscape and incorporates closed-loop adaptive algorithms to consistently challenge the participant at a high level, an approach which is thought to optimize training effects (Mishra et al, 2016;Ziegler et al, 2022) and lead to transfer of benefits to an array of cognitive abilities (Anguera et al, 2013(Anguera et al, , 2022Mishra et al, 2014;Nandi et al, 2023;Wais et al, 2021;Zanto et al, 2022;Ziegler et al, 2019). It was played in the classroom on an iPad tablet that permits tapping on the screen akin to certain types of drumming.…”
Section: Digital Rhythm Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed the effect of musical training ( George and Coch, 2011 ; Wong and Gauthier, 2012 ; Matthews et al, 2018 ), even late or short musical training ( Wong et al, 2019 ; Che et al, 2022 ; Zanto et al, 2022 ), on visual perception, but no study has examined the effect of musical training on visual perception associated with the Gestalt principles as far as we know. Through the Visual Closure subset from the MVPT, the current study confirms our hypothesis that, unlike late musical training, early musical training is beneficial to non-musical cognitive ability associated with Gestalt-like ability.…”
Section: Discussionmentioning
confidence: 99%
“…Different frequencies of sound vibration can affect a wide range of neurological and physiological functions, gamma waves (around 40 Hz) having significant effects on various levels of neural plasticity (reviewed in Bartel and Mosabbir, 2021). Music is of course made up of a vast array of sound frequencies and has been shown to have measurable effects on oscillatory activity (Thaut et al, 2005;Fujioka et al, 2015;Kučikienė and Praninskienė, 2018;Yurgil et al, 2020;Lerousseau et al, 2021;Yang et al, 2022;Nandi et al, 2023). Interestingly then, in subjects listening to preferred music, EEG recordings revealed reduced low frequency oscillations associated with lower ratings of pain (Lu et al, 2019), and Gu et al (2020) reported that, compared to happy or neutral music, sad music was the most effective in alleviating pain, associated with altered brain oscillations in beta and gamma bands.…”
Section: Spinal Cord and Brainstemmentioning
confidence: 99%